Comparison of the efficacy and safety of fruquintinib and regorafenib in the treatment of metastatic colorectal cancer: A real-world study - Deng, Ya-Ya; Zhang, Xin-Yue; Zhu, Peng-Fei; Lu, Hong-Rui; Liu, Qian; Pan, Shuang-Yue; Chen, Zhe-Ling; Yang, Liu (Frontiers in Oncology, 2023)
Background Fruquintinib and regorafenib have been approved for the third-line therapy of metastatic colorectal cancer (mCRC) in China. However, at present, there is a lack of head-to-head clinical trials on the comparison of efficacy and safety between the two drugs. Materials and Methods: We collected and analyzed the efficacy and safety data of patients with mCRC who were treated with fruquintinib or regorafenib after the standard chemotherapy in Zhejiang Provincial People's Hospital from October 2018 to November 2021. Results: A total of 105 patients were enrolled in this study. The ORR of fruquintinib group (n=55) and regorafenib group (n=50) were 6.1% and 2.0%; the DCR were 65.3% and 54.2%, respectively. There was no significant difference in median OS (mOS) and PFS (mPFS) between the two groups (mOS:14.2 vs12.0 months, p=0.057; mPFS:4.4 vs 3.5 months, p=0.150). Combined immunotherapy showed a synergistic effect. The mPFS and mOS of fruquintinib combined with anti-PD-1 therapy were longer than those of fruquintinib monotherapy (mPFS:5.9 vs 3.0 months, p=0.009; mOS:17.5 vs 11.3 months, p=0.008). The mOS of patients treated with regorafenib combined with anti-PD-1 therapy was 14.8 months higher than that of regorafenib monotherapy (p=0.045). When combined with anti-PD-1 therapy, the mPFS and mOS of fruquintinib was significantly longer than regorafenib (mPFS:5.9 vs 3.8 months, p=0.018; mOS:17.5 vs 14.8 months, p=0.044). In the treatment sequence, the OS of patients treated with regorafenib and then fruquintinib was significantly longer than that of the reverse treatment sequence (15.0 vs 8.3 months, p=0.019). The adverse reactions were generally similar, but the incidence of hand-foot syndrome of regorafenib was higher than that of fruquintinib, while fruquintinib was more prone to grade 3 hypertension. Conclusion: Fruquintinib monotherapy showed better disease control rate and objective remission rate in the post-line therapy of metastasis colorectal cancer. Notably, the combination of PD-1 immunotherapy brought the additional effect, especially in the fruquintinib combined with anti-PD-1 therapy. Patients treated with regorafenib and then fruquintinib was significantly longer than that of the reverse treatment sequence. The toxicity of fruquintinib and regorafenib are similar.